PENGARUH KEPEMIMPINAN KEPALA MADRASAH TERHADAP KELENGKAPAN ADMINISTRASI PEMBELAJARAN DI MTS BAHRUL ULUM DESA AIR EMAS KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Khalimatus Sakdiyah; Helbi Akbar; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
The Background Of the researcher took this titel is the researcher wanted to know how the influence of the Leadership of the head of Madrasah In MTs Bahrul Ulum Village water Gold subdistrict Singingi distric Kuantan Singingi. As for the Formulation of the Problem the researcher is like where the influence Lendership of the Madrasah Head towards the completeness of the Learning Administration in the MTs Bahrul Ulum Village Water gold Sub-district Singingi Regency Kuantan Singingi, How The Administration of learning in the MTs Bahrul Ulum Village of the Golden Water District Of the District Singingi Was Singingi. This research was carried out at the MTs BahrulmUlum Village sub-district gold water singingi kabu patent kuantan singingi the technique of Collecting date is Through Study Interviews, Observation, doccumentation, Quesitionnaires and then the Researchaers Analyze Denfan’s date Using Quantitative Methods, Date Collection is Done by Submitting a questionnaire to the Respondent Namely The Head of the Madrasah and The Techer at the MTs Bahrul Ulum Village water Gold Sub- district singingi District Kuantan Singingi. The Results of this study indicate that there is a significant Influence of the Headmaster’s Lendership Between the headmaster’s lendership variabel on the completeness of the learning Administration in the MTs Bahrul Ulum Village of the golden water district singingi. This can be seen from the determentcoefficient of 0.737881 which means that there is an influence of the headmaster’s leadership on thelearning administration in the MTs Bahrul Ulum Village, The district singingi district i am singingi,while the test a Positive influence between the leadship of teh madrasah head towards the administrative completeness of of the lessons in the MTs Bahrul Ulum. This can be seen from the value Y=1. 068 + X 1.025 meaning that Ho is rejected and Ha is accepted. Therefore there is the influence of the completeness of the learning adminisration at MTs Bahrul Ulum Village water Gold sub-discrit Singingi discrit Kuantan Singingi.